Read All About : HORSES - Nadia Ali (Read All About It!, 2023)
"Did you know that horses can sleep standing up? Or that horses have the largest eyes of any land mammal? Find out all about horses' senses, life cycle, behavior, and more in this fact-filled book. Stunning photos give readers an up-close look at these loyal, majestic companions that have been living and working alongside people for thousands of years."